Pengaruh Penambahan Serat Kulit Jagung Terhadap Sifat Mekanik Komposit High Density Polyethylene (HDPE) dengan Aluminium Oksida (Al2O3) dan Maleat Anhidrida (MAH) sebagai Coupling Agent - Herlin Arina; Melyna, Ella; Salsabila, Shafiyah (Jurnal Inotera, 2024)
The application of composites is widely used in the automotive field. HDPE, a versatile polymer, is frequently employed as a composite matrix, combining with other materials to produce unique mechanical properties and characteristics. Its widespread application in the automotive sector includes the manufacturing of bumpers and car interiors, where its distinct properties enhance the overall performance and functionality of these components. Corn husk fiber waste is a natural material that has not been utilized properly, so the use of corn husk fiber as reinforcement in composites is an alternative to waste problems in the environment. Aluminum Oxide (Al2O3) as a filler with another name alumina, possesses strong tensile strength and thermal stability, and it is anticipated to lower production costs while enhancing composites' mechanical qualities. Maleic anhydride (MAH), a coupling agent, is applied to the matrix, reinforcement, and filler to increase their adherence. The manufacture of HDPE matrix composite with the addition of corn husk fiber and MAH is expected to improve the mechanical properties of the composite. The composition of HDPE: corn husk fiber (%wt) is 90:0, 85:5, and 80:10, as well as the composition of 5%wt alumina and 5%wt MAH in each sample. Making composite pellets using a compounder, making composite sheets by hot press method using a manual forming machine. Tensile strength and hardness measurements were taken to evaluate material performance. Tensile strength testing was carried out using a Universal Testing Machine (UTM), crystallinity testing using Differential Scanning Calorimetry (DSC) and testing using Near-Infrared (NIR). The tensile strength test results obtained the highest tensile strength value in the composition of HDPE: corn husk fiber 90: 0%wt of 17.67 MPa. The crystallinity test results obtained the highest degree of crystallinity in the composition of HDPE: corn husk fiber 90: 0%wt of 67.88%. The incorporation of corn husk fibers into the composite material significantly affects its mechanical properties, particularly the tensile strength and crystallinity, with higher fiber content leading to a notable reduction in these properties. SEM testing was also carried out to determine the morphological shape of the composite.